2012
DOI: 10.1073/pnas.1210350109
|View full text |Cite
|
Sign up to set email alerts
|

Euler and Navier–Stokes equations on the hyperbolic plane

Abstract: We show that nonuniqueness of the Leray-Hopf solutions of the Navier-Stokes equation on the hyperbolic plane H 2 observed by Chan and Czubak is a consequence of the Hodge decomposition. We show that this phenomenon does not occur on H n whenever n ≥ 3. We also describe the corresponding general Hamiltonian framework of hydrodynamics on complete Riemannian manifolds, which includes the hyperbolic setting.harmonic forms | steady flows | ill-posedness | Dirichlet problem | Dodziuk's theorem C onsider the initial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…In [17], by means of the result of Dodziuk [7], Khesin and Misio lek showed that our construction can only work in 2D. The main idea is that on H n (−a 2 ) the only L 2 harmonic forms are of degree k = n 2 .…”
Section: Other Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [17], by means of the result of Dodziuk [7], Khesin and Misio lek showed that our construction can only work in 2D. The main idea is that on H n (−a 2 ) the only L 2 harmonic forms are of degree k = n 2 .…”
Section: Other Dimensionsmentioning
confidence: 99%
“…To see this, we could use the result of [7] to know that dF belongs to L 2 (H 2 (−a 2 )) since it is a harmonic 1-form, and H 2 (−a 2 ) satisfies properties of the manifolds considered in [7]. More directly, as done in [17] and in [26] one can use the conformal equivalence of the Poincaré disk and the Euclidean unit disk together with standard elliptic theory to show that dF is in L 2 . However, to treat more general Riemannian manifolds, we would still need (1.10).…”
Section: Simpler Proofsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a little catch here [19]. In fact, L 2 (Vect χ ) splits into a direct orthogonal sum of two subspaces…”
Section: Hyperbolic Planementioning
confidence: 99%